KARYA TARI “FAKE SMILE” BERBASIS RISET - Rahmat Elfi Julianto; Wardi Metro; Idun Ariastuti (Laga-Laga : Jurnal Seni Pertunjukan, 2021)
The dance work "Fake Smile" was inspired by personality disorders that exist around society, namely psychopaths. Psychopath, which is a condition in which a person cannot feel empathy and tends to commit violence to other humans without being followed by feelings of guilt for his own satisfaction. In working on this concept, the writer has an idea that is to use facial and body expressions as a medium of expression and communication as well as the property of a pyramid-shaped frame covered with cloth as an expression of the mood of a psychopath. In addition, the exploration of motion is developed from the behavior of people with psychopathic disorders which are visualized with the character of the writer. The methods used in this work include observation, data processing, literature study, selection of supporting works, exploration, motion arrangement, improvisation, and evaluation. This work consists of three parts, the first part describes the anti-social pressure, the second part describes the emotional sufferer, and the third part describes the uncontrolled body of the psychopath sufferer.